A Sari For Ammi - Nainy, Mamta; Prabhat, Sandhya (New York : Amazon Crossing Kids, 2021)
"Ammi weaves the most beautiful saris but never gets to wear any of them. Her two little daughters decide to do something about it--break their piggy bank! But when there isn't enough money to buy Ammi a sari, the two girls must work together to find a solution. Will they be able to buy Ammi the gift she so deserves? With a text full of heart, and bright, cheerful artwork, this story brings readers into the home of a weaver's family in Kaithoon, India, where the creation of saris is an art form. The bookincludes a glossary of Indian terms and a note about the saris made in this region"--.
new kids book 2025 summer.
Keywords: Saris -- Fiction; Women's clothing -- India -- Fiction; Weavers -- India -- Fiction; Families -- India -- Fiction; India -- Fiction